Genetic analysis on grain physical characteristics and grain color from the crosses of black × white rice genotypes - Siti Nurhidayah; PANJI HANDOKO BADIARAJA; HERU TOTOK AGUNG D. HARYANTO; PRITA SARI DEWI (Society for Indonesian Biodiversity, 2021)
Abstract. Nurhidayah S, Firmansyah E, Haryanto TAD, Dewi PS. 2021. Genetic studies of grain physical characteristics and grain color from the crosses of black × white rice genotypes. Biodiversitas 22: 2763-2772. This study was conducted to investigate genetic variance, cytoplasmic maternal effect, gene action, and broad-sense heritability of grain physical characteristics and grain color from crosses of black × white rice genotypes (Oryza sativa). Genetic studies were conducted using F2 generations from the crosses of black × white rice genotypes and their reciprocal crosses. The plant materials consisted of seven black rice genotypes (PH2, PH3, PH4, PH5, PH6, PH7, and PH8), three commercial white rice varieties (Inpari 13, Inpari 18, and Inpari 19), a total of 30 F2 generations, and their reciprocal crosses. There are four-grain physical traits examined: grain length, grain width, grain thickness, and grain color. The result showed that maternal cytoplasmic effect was present in most F2 generations and their reciprocal crosses. The characters of grain length, grain width, and grain thickness are controlled by polygene with additive action. Based on the results of the Chi-Square Test, the grain color did not follow the expected 1: 2: 1 ratio for incomplete dominance involving monogenic traits. Broad sense heritability for grain length, grain width, and grain thickness are varied from low to medium for a cross of black rice genotypes × Inpari 19, and low to high for the crosses of black rice genotypes × Inpari 13 and black rice genotypes × Inpari 18.